“The Impact of Traditional Games on Enhancing Students’ Compositional Skills in Fine Arts” - Xidoyeva Mahliyo Bozor qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores how traditional national games can enhance compositional skills in students during fine arts lessons. It discusses the pedagogical benefits of integrating game-based activities into art education, including fostering creativity, spatial awareness, emotional expression, and cultural understanding. Practical strategies for teachers are also highlighted to make lessons more interactive and effective.